Hazard Factors and Preventive Measures in Pesticide Formulation Processing and Production - Yang, Jun (International Journal of Agriculture and Food Sciences Research, 2025)
The production of pesticide formulations is characterized by highly toxic materials, complex processes, and significant risks, posing severe challenges to production safety. Based on the characteristics of pesticide formulation production processes, this paper systematically analyzes hazard factors in physical, chemical, and process aspects during production. It examines mechanical injuries, noise hazards, electrical risks, toxicity hazards, fire and explosion risks, corrosion hazards, operational risks, equipment failures, and storage and transportation dangers. Corresponding preventive measures are proposed for each type of hazard, including improving protective systems, enhancing process management, and establishing emergency response mechanisms. These recommendations aim to provide theoretical and practical guidance for improving the safety level of pesticide formulation production.